Workplace Dynamics and Millennial Satisfaction in Startups: Investigating the Influence of Intensification, Flexibility, and Life Balance - Adiba, Naura Indah; Rialmi, Zackharia (PT. Sangadji Media Publishing, 2025)
Purpose – This study aims to investigate the effect of work intensification, work-life balance, and work flexibility on job satisfaction among millennial employees working in startup companies located in RW 15, Rangkapan Jaya Village, Pancoran Mas District, Depok City. The research addresses a significant gap in the literature by focusing on HR dynamics in small-scale startup contexts in Indonesia. Design/method/approach – A quantitative cross-sectional design was employed, utilizing a saturated sample of 38 respondents. Data were collected through a structured questionnaire comprising validated scales for each variable. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0, incorporating validity and reliability checks and bootstrapping for hypothesis testing. Findings – The results indicate that all three independent variables—work intensification, work-life balance, and work flexibility—have a significant and positive effect on job satisfaction. Among them, work flexibility exerted the strongest influence, followed by work-life balance and work intensification. Implications – Explain the theoretical or practical significance of your findings. This may include policy recommendations, managerial insights, or contributions to academic literature. Keep it concise but impactful. Novelty/Originality – This research is distinct in its localized focus on millennial employees in startup environments within a single urban neighborhood in Indonesia. By integrating three critical constructs—work intensification, work-life balance, and work flexibility—into a single model, the study offers a novel and context-sensitive understanding of job satisfaction determinants.